Self-powered GPS tracking system for vehicle and asset monitoring - Tolentino, Ian Christopher Magana
We describe the design and development of a self-powered tracking system for vehicle security applications. A vibration energy harvester was designed based on a test vehicle?s vibration profile. Three piezoelectric generators, configured in cantilever beam configurations and arranged in a radial topology, were tuned to the dominant frequency of the application and were used to convert mechanical vibrations to electrical energy. Voltage doublers were used for rectifying the sinusoidal piezoelectric outputs and to isolate the piezoelectric generators for each other. By using only the rectified piezoelectric outputs, the harvester is able to adapt to changes in vibration frequency and magnitude and keep its operating point as close as possible to the maximum power point (MPP). The harvester is able to operate with up to 70.86% efficiency and 19.8mW output as power, consuming a maximum of 200uW. The harvester operates with 5% of the MPP as the load is charged from 2.5V to 5.5V. Even with a deviation of 30% from the nominal vibration magnitude and 1Hz deviation from the nominal frequency, the harvester operation is kept within 1% and 6% of the MPP respectively. A 2-tank energy storage unit composed of a supercapacitor and a Li-Ion battery was implemented to store the energy harvested from mechanical vibrations. The 1F supercapacitor, which serves as secondary energy storage, supplies power to the harvester while the Li-Ion battery is still being charged. The stored energy is used to power the harvester circuitry, the control unit, and the tracking unit composed of a GPS and a GSM module. The tracking unit was tested by attaching it to the rear axle of the test vehicle. The operation and performance of the overall system were evaluated using the actual vibration profiles of the test vehicle.